Impact of Pharmacists to Improve Patient Care in the Critically Ill: A Large Multicenter Analysis Using Meaningful Metrics With the Medication Regimen Complexity-ICU (MRC-ICU) Score*. Issue 9 (15th August 2022) - Sikora, Andrea; Ayyala, Deepak; Rech, Megan A.; Blackwell, Sarah B.; Campbell, Joshua; Caylor, Meghan M.; Condeni, Melanie Smith; DePriest, Ashley; Dzierba, Amy L.; Flannery, Alexander H.; Hamilton, Leslie A.; Heavner, Mojdeh S.; et al.
Abstract : OBJECTIVES: Despite the established role of the critical care pharmacist on the ICU multiprofessional team, critical care pharmacist workloads are likely not optimized in the ICU. Medication regimen complexity (as measured by the Medication Regimen Complexity-ICU [MRC-ICU] scoring tool) has been proposed as a potential metric to optimize critical care pharmacist workload but has lacked robust external validation. The purpose of this study was to test the hypothesis that MRC-ICU is related to both patient outcomes and pharmacist interventions in a diverse ICU population. DESIGN: This was a multicenter, observational cohort study. SETTING: Twenty-eight ICUs in the United States. PATIENTS: Adult ICU patients. INTERVENTIONS: Critical care pharmacist interventions (quantity and type) on the medication regimens of critically ill patients over a 4-week period were prospectively captured. MRC-ICU and patient outcomes (i.e., mortality and length of stay [LOS]) were recorded retrospectively. MEASUREMENTS AND MAIN RESULTS: A total of 3, 908 patients at 28 centers were included. Following analysis of variance, MRC-ICU was significantly associated with mortality (odds ratio, 1.09; 95% CI, 1.08–1.11; p < 0.01), ICU LOS (β coefficient, 0.41; 95% CI, 00.37–0.45; p < 0.01), total pharmacist interventions (β coefficient, 0.07; 95% CI, 0.04–0.09; p < 0.01), and a composite intensity score of pharmacist interventions (β coefficient, 0.19; 95% CI, 0.11–0.28; p < 0.01). In multivariable regression analysis, increased patient: pharmacist ratio (indicating more patients per clinician) was significantly associated with increased ICU LOS (β coefficient, 0.02; 0.00–0.04; p = 0.02) and reduced quantity (β coefficient, –0.03; 95% CI, –0.04 to –0.02; p < 0.01) and intensity of interventions (β coefficient, –0.05; 95% CI, –0.09 to –0.01). CONCLUSIONS: Increased medication regimen complexity, defined by the MRC-ICU, is associated with increased mortality, LOS, intervention quantity, and intervention intensity. Further, these results suggest that increased pharmacist workload is associated with decreased care provided and worsened patient outcomes, which warrants further exploration into staffing models and patient outcomes.